The effect of ensiled maize grains on laying of hens - Eva TKALČIČ; Jasna M.A. STEKAR; Milena KOVAČ; Antonija HOLCMAN (Acta Agriculturae Slovenica)
In the feeding trial with 600 laying hens of ISA Brown provenance the effect of ensiled maize grains on laying was examined. The laying was monitored since the age 21 weeks. At the age 32 weeks from the flock of 1400 hens 600 animals were chosen at random and divided in six groups. Trial rations were started at age 40 weeks when the hens reached the peak production. The trial had lasted for 154 days when the laying capacity started to decrease considerably. Two maize hybrids Raissa and Lotus were compared. In the ration there were 40% of dry matter from ensiled grains or 60% respectively. Supplemental feeding mixture was equal in both cases. Control animals were fed with complete feeding mixture ad libitum. Other groups fed with silage as well as one group of laying hens fed with complete feeding mixture were given restricted rations. Results of laying before and during the trial were processed by statistical package SAS/STAT (1990). There were no significant differences between the hybrids. Groups with 40% dry matter from the silage had significantly lower laying than the control group, which can be explained by lower energy content. Groups with 60% of dry matter from the silage had better laying than the groups with less silage as well as better laying in comparison with the control groups. Groups with higher metabolic energy content in trial ration had better laying. Energy and protein consumption for egg production differed a lot between the groups due to different contents of protein and energy in the rations and, hence, to diverse number of laid eggs.